ACCP clinical pharmacist competencies: Advocating alignment between student, resident, and practitioner competencies. Issue 1 (8th January 2020) - Engle, Janet P.; Burke, John M.; Ashjian, Emily J.; Avery, Lisa; Borchert, Jill S.; Faro, Sara Jane E.; Harris, Christy S.; Herink, Megan C.; Jain, Barkha; MacLaughlin, Eric J.; Martello, Jay L.; Moore, Katherine; et al.
Abstract: Competency standards in pharmacy education and training have been formulated by different organizations to focus on various stages in the development of students, residents, and clinical pharmacists. This commentary advocates a deliberate alignment of educational outcomes, goals, and competencies across the developmental continuum of students, residents, and pharmacy practitioners. Consistent use of terminology and appropriate sequencing of expectations will help develop pharmacists who can meet the demands of the profession in the changing health care landscape. Progressive development is needed for the pharmacist's abilities, from student to resident to new practitioner to experienced professional. Consistency will ensure that educational and training programs optimally prepare individuals for board certification and professional roles. Specific recommendations include developing a common taxonomy that aligns within the pharmacy profession and across health care professions.